The Influence of Digital Leadership and Data Literacy on Managerial Effectiveness Through Work Motivation: A Study of Private Vocational School Principals in Jakarta - Ahmad Kosasih; Soewarto Hardhienata; Herfina Herfina (International Research of Multidisciplinary Analysis, 2026)
The digital transformation of vocational education demands that school principals possess high levels of managerial effectiveness; however, the gap between expectations and reality remains a significant challenge. This study aims to examine the influence of digital leadership and data literacy on managerial effectiveness, both directly and indirectly, through work motivation. Employing a quantitative approach with a cross-sectional survey design, the study involved 206 teachers from 19 private vocational high schools (SMK PGRI) in Jakarta, Indonesia. Data were collected using a validated 5-point Likert scale questionnaire. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results show that: (1) digital leadership has a positive and significant direct effect on managerial effectiveness (β = 0.291; p < 0.001); (2) data literacy has a positive and significant direct effect on managerial effectiveness (β = 0.174; p = 0.010); and (3) work motivation significantly mediates the effects of digital leadership (indirect effect = 0.065; p = 0.021) and data literacy (indirect effect = 0.036; p = 0.046) on managerial effectiveness. These findings confirm that enhancing managerial effectiveness is optimally achieved through simultaneously strengthening digital competencies and work motivation.